Semi-Welded Plate Heat Exchangers Applications and Development in Refrigeration Systems (Zhileng xuebao)
For promoting energy economy and environmental protection in refrigeration system, Alfa Laval has developed new version of Semi-welded plate heat exchangers by continuous R&D. Practice proved that it solves the existed technical problems such as refrigerant permeation, damage by frozen, stress fatigue, etc. while holding the advantages of common ones. New technologies make Semi-welded plate heat exchangers modulize and be widely used by refrigeration application. The optimization software ensures the investment be the lowest in whole system.